Meningkatkan Aktivitas serta Hasil Belajar Mengenal Malaikat dan Tugasnya melalui Metode Smart Game dengan Pembelajaran Kooperatif Make A Match pada Siswa Kelas IV SDN 36 Gedong Tataan Tahun 2020 - Siaga Dewi (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2023)
This research was carried out due to the need to increase teacher teaching creativity in managing the PAI learning process in elementary schools as a response to the weakening quality of student learning. This study uses the Smart Game Method and Cooperative Learning Type Make A Match with the aim of increasing activity and learning outcomes in PAI learning. The research was conducted at SDN 36 Gedong Tataan on the basic competence of knowing angels and their duties. The results of the study show that the use of the Smart Game Method and the Make A Match Type Cooperative Learning Method can increase the activity and learning outcomes of fourth grade students at SDN 36 Gedong Tataan Pesawaran in 2020.